Cálculo espectral de la irradiación solar directa, difusa y global en Heredia, Costa Rica (ING) - Wright, Jaime (2008)
A clear sky solar spectral model which describes the irradiation flux has been tested experimentally in Heredia, Costa Rica. A description of the model and comparisons with radiation data are presented. The model computes spectral fluxes of direct, diffuse and global solar irradiation incident on a horizontal surface. Necessary inputs include latitude, altitude, and surface albedo as characteristics of a location as well as the atmospheric characteristics: turbidity, precipitable water vapor, and total ozone content. The results evidence a satisfactory agreement.